Description Of Local Pigs Histopathology in Small Islands of North Sulawesi - Revolson Alexius Mege; Mery Friska Montolalu; Rolef Rumondor; Nonny Manampiring (Indonesian Biodiversity Journal, 2020)
Some areas in Indonesia have local pigs with their own special characteristics. One of them is North Sulawesi which has local pigs that are maintained by the population with a traditional system and some live wild. The liver is the largest gland that has an important function for living things. This study aims to determine the histology of native pig liver from small islands in North Sulawesi. The liver is histopathologically processed with hematoxylin-eosin staining and then the preparation is analyzed descriptively. The results showed a histological picture in the Buhias and Bunaken areas showing necrosis and widening of the sinusoid while histological features in the Kahuku, Bangka, and Nain regions showed that the liver had severe steatosis and cirrhosis of the liver.